Crescimento urbano, impactos ambientais e percepção ambiental na sub-bacia do rio Tibiri, Santa Tita – Paraíba - Pereira, Felipe Julião (2023)
Urban growth is predominantly driven by increased economic activities, manifesting itself through the demand for built-up areas, creating anthropic landscapes, putting pressure on the natural environment. This phenomenon can be identified in several regions of the world, as is the case of Santa Rita, municipality of Paraíba, northeastern Brazil. The municipality has undergone intense urban expansion in recent decades, resulting in several environmental problems, especially in aquatic environments. Among these, the Tibiri River stands out, responsible for supplying water to part of the urban population and serving as a source of recreation, leisure and fishing. With that, the main objective of this study was to evaluate the urban growth and the environmental impacts in the Tibiri River sub-basin in Santa Rita, Paraíba, resulting from the urbanization process. This research has a quali-quantitative approach where bibliographic research and case study were used as techniques. The urbanization process was evaluated based on a bibliographic survey and the elaboration of maps of land use and occupation in the QGIS software from the 1980s, using the MapBiomas database. In order to identify the environmental impacts, visits were made during the rainy and dry periods to use the checklist method based on the adaptation of the Rapid Assessment Protocol proposed by Callisto et al., (2002) and the creation of an environmental quality index adapted from Campos and Nucci (2019). The survey of environmental perception regarding the problems of urbanization, water resources, environmental impacts and basic sanitation service was carried out based on 400 semi-structured interviews, with the analysis of the interviews based on simple descriptive statistics and the categorization of responses with based on Content Analysis proposed by Bardin (2016). Finally, the proposals for solutions to the identified problems were proposed based on a bibliographic survey. The data revealed that 86% of the population of Santa Rita resided in the urban area in 2010, with the greatest period of urban population growth being between the 1970s and 1980s. Urban expansion in the sub- basin took place mainly in the 1980s, with the creation of Bairro dos Municípios and subdivisions on the left bank of the Tibiri River. The economy of Santa Rita is boosted by several industries, service and commerce companies and by agribusiness, being a housing option for workers from other regions of the State who seek residences close to the capital at a lower cost. The land use and occupation maps revealed a reduction in the area of the “Agriculture” class and an increase in the areas of the “Non-vegetated area” and “Forest” classes. The environmental impacts in the Tibiri River sub-basin revealed that three points in the upper course of the river are classified as “Good” and in the lower course one point was classified as “Regular” and one as “Bad”. Regarding environmental perception, the systemic view category was the most evident in the evocations in relation to the impacts of urbanization, problems of sewage and solid waste in rivers. The proposals for improvements were related to ecological sanitation, urban drainage, selective collection and environmental education, and for the recovery of the river, bioremediation actions with biofilm were proposed. It is emphasized that due to the current situation of the Tibiri River, there is an urgent need to establish mitigation measures in order to avoid the increase in the degradation of this river. These measures will bring numerous environmental and social benefits, requiring a joint effort by public authorities and society.